Range and throughput enhancement of wireless local area networks using smart sectorised antennas. - Doufexi, A. (IEEE Transactions on wireless communications)
At present, wireless local area networks (WLANs) such as HiperLAN2 and 802.11a are being developed and deployed around the world. In this letter, the use of sectorized antennas is considered as a means to improve the physical layer performance of WLANs. Results demonstrate that throughput and range can be enhanced and/or the transmit power can be reduced. However, these benefits are achieved with a small increase in multiple access protocol overhead. Simulations are performed using measured wideband channels in the 5-GHz band. In cases where the channel exhibits strong Rician characteristics, gains as high as 13 dB are demonstrated. These benefits substantially outweigh the associated medium access control overhead.